1969
DOI: 10.1021/ja01034a023
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of cephalosporin antibiotics. XV. Transformations of penicillin sulfoxide. Synthesis of cephalosporin compounds

Abstract: A procedure for obtaining compounds containing the cephalosporin ring system from penicillins embodying a new general reaction of cyclic sulfoxides, an intramolecular oxidation-reduction in which a carbon p to the sulfur is oxidized, has been developed. Products resulting without rearrangement of the sulfur ring (the substituted penicillin 4), with ring expansion (cephalosporins 5 and 6) and with ring contraction (compound 15) have been observed. Speculations concerning mechanisms ai16 stereochemistry are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(52 citation statements)
references
References 3 publications
0
51
0
1
Order By: Relevance
“…Cycloheximide, kanamycin, and streptomycin are also reported to inhibit the protein synthesis, but they do not inhibit the growth of Gram-positive bacteria (Madigan et al, 2000). Cephalexin and cycloserine inhibit the cell wall synthesis, and mitomycin C inhibits DNA synthesis (Iyer and Szybalski, 1964;Morin et al, 1969;Neuhaus and Lynch, 1964). As mentioned above, antibiotics influence biosyntheses, and induced the cystite formation of A. ureafaciens NRIC 0157 T .…”
Section: Discussionmentioning
confidence: 94%
“…Cycloheximide, kanamycin, and streptomycin are also reported to inhibit the protein synthesis, but they do not inhibit the growth of Gram-positive bacteria (Madigan et al, 2000). Cephalexin and cycloserine inhibit the cell wall synthesis, and mitomycin C inhibits DNA synthesis (Iyer and Szybalski, 1964;Morin et al, 1969;Neuhaus and Lynch, 1964). As mentioned above, antibiotics influence biosyntheses, and induced the cystite formation of A. ureafaciens NRIC 0157 T .…”
Section: Discussionmentioning
confidence: 94%
“…This trend is seen in the solid state (14), and is reflected (15,16) in the different p-lactam carbonyl stretching frequencies of these compounds (15: 1790 cm-';…”
mentioning
confidence: 81%
“…It was proposed that this transformation was mechanistically analogous to the Morin rearrangement of penams to cephams. 42 In fact, it had been hoped that the presumed intermediate N-acyliminium ion 91 might initiate the double cyclization sequence outlined in Scheme 14, but this was not the case; 92 was a dead end as studies with CF 3 CO 2 D indicated that it was not protonated to give 91. It is also notable that isomers 97 and 98 are in equilibrium under the reaction conditions.…”
Section: Scheme 14mentioning
confidence: 99%